Traditional (Culinary) Markets as A Tourist Village during The COVID-19 Pandemic and Post-COVID-19 Period: A Socio-Legal Study - Mangunsong, Nurainun; Hanum, Willy Naresta; Kwarteng, Abdul Hamid (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
Village tourism is one of the flagship projects and tourism development priorities of the Yogyakarta Regional Government (DIY Regional Regulation No. 1 of 2019) to optimize the potential of village resources to improve the welfare and economic independence of village communities (Law No. 6 of 2014). To optimize the policy, the DIY Government has developed a management system in the 2015–2025 Regional Tourism Development Master Plan with the facilitation of a Tourism Village Pioneer towards an Independent Tourism Village. The management includes the planning, implementation, and control of tourism village activities. This study will examine the implementation and dynamics of regulations during the COVID-19 pandemic and post-COVID-19. To explain and measure the policy, an empirical (socio-legal) study was conducted on one of the tourist villages, "Pasar Kuliner Belik Sonto" Sleman, as a sample, which had received a grant from the Ministry of Tourism in 2021 for a pilot tourism village management model. The study results concluded that the governance of tourist villages such as the Belik Sonto Gamplong I Traditional Culinary Market during the COVID-19 period did not appear optimal. It is due to the lack of conceptual standardization of institutional governance and in terms of regulations. Meanwhile, post-COVID-19, tourism village governance entering the recovery and normalization phase needs to reformulate tourism village development plans and resources towards resilient and superior tourism villages through product innovation, synergy between various parties, the government, and related regional apparatuses, collaborative variations of tourism village events, and the development of marketing systems. This governance fully adapts to various post-COVID-19 mitigation regulations by developing tourism village safety and health infrastructure.